PENERAPAN PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN PRESTASI BELAJAR BAHASA ARAB DI MADRASAH IBTIDAâIYAH AL-IMAM METRO KIBANG LAMPUNG TIMUR TP.2010/2011) - Akla, Akla, (JURNAL TAPIS, 2011)
The studentsâ facing difficulties in digesting the material has become a problem in Arabic instruction. Many factors can be listed such as monotonous teaching method, inadequate teaching aid, and so on. To cope with the problems, Quantum Teaching model could be an alternative. This model is accelerated learning model with Quantum learning method. The accelerated learning means acceleration program by reducing the obstacles that hamper natural process of study through intentional efforts. The problem formulation of this research is whether Quantum Teaching approach can increase Arabic language study achievement of the students of MI Al-Imam Metro Kibang, East Lampung in the academic year of 2010/2011. This research is aimed at knowing the raising of Arabic language study achievement of MI Al-Imam Metro Kibang, East Lampung in the academic year of 2010/2011 through Quantum teaching approach. The data collecting method used were observation, test and documentation.Based on three cycles of implementation, it can be inferred that there is a significant rising of Quantum Teaching approach toward Arabic language study achievement. The evaluation result of each cycle is continued to T-test. The result of the study shows that Quantum teaching can increase Arabic language study achievementÂ  of the students of MI Al-Imam Metro Kibang, East Lampung.Keywords: Pembelajaran, Quantum Teaching, Prestasi Belajar dan Bahasa Arab